2013
DOI: 10.1175/mwr-d-13-00033.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Forcings on Prediction of the North Atlantic Oscillation Regime of Winter 2010/11

Abstract: December 2010 was unusual both in the strength of the negative North Atlantic Oscillation (NAO) intense atmospheric blocking and the associated record-breaking low temperatures over much of northern Europe. The negative North Atlantic Oscillation for November-January was predicted in October by 8 out of 11 World Meteorological Organization Global Producing Centres (WMO GPCs) of long-range forecasts. This paper examines whether the unusual strength of the NAO and temperature anomaly signals in early winter 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 57 publications
4
58
0
Order By: Relevance
“…This is consistent with the conclusions of Maidens et al (2013), who found that Atlantic SSTs were a major contributory factor to the negative NAO of this year. Interestingly though, in both models around 50% of the negative forcing comes from west Indian Ocean rainfall, which is indicative of convective activity and divergence leading to Rossby wave propagation.…”
Section: A Deterministic Hindcastssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the conclusions of Maidens et al (2013), who found that Atlantic SSTs were a major contributory factor to the negative NAO of this year. Interestingly though, in both models around 50% of the negative forcing comes from west Indian Ocean rainfall, which is indicative of convective activity and divergence leading to Rossby wave propagation.…”
Section: A Deterministic Hindcastssupporting
confidence: 93%
“…In addition, N80 shows an extratropical influence from the June North Atlantic tripole, while in N93 the October AMO is selected as a predictor and solar forcing is also significant in the longer time series. The solar forcing term here is at a lead of around 3 yr, consistent with that identified from other studies (Scaife et al 2013;Gray et al 2013;Andrews et al 2015). A number of very similar correlations are found at lead times ranging from 6 months to 3 yr.…”
Section: A Deterministic Hindcastssupporting
confidence: 90%
See 1 more Smart Citation
“…In models, the NAO-negative Here we attribute the dipole pattern of warm tropical waters and cold subtropical waters (two-thirds of the tripole pattern) to the 30 % slowdown in the AMOC. In a seasonal forecast for the winter of 2010-2011 over northwestern Europe, it was found that the distribution of upper ocean temperature anomalies in October-November 2010 was the key factor allowing severe winter conditions to be successfully forecast 3 months in advance (Maidens et al, 2013). On this basis we argue that the AMOC slowdown created an upper ocean temperature distribution that helped push the atmospheric circulation into record-low NAO negative states in both the winters of 2009-2010 and 2010-2011 with consequent effects on UK winter weather (Osborn, 2011).…”
Section: Response Of the Atmosphere To The Rapid Eventmentioning
confidence: 99%
“…The resultant northward heat transport within the North Atlantic affects both the long-term climatic state over northern Europe (Trenberth and Caron 2001;Johns et al 2011) and the interannual climate variability across the North Atlantic basin (Maidens et al 2013). This interannual variability can be very pronounced.…”
Section: Introductionmentioning
confidence: 99%